Physical Layer Security of Dual-Hop Hybrid FSO-mmWave Systems - Saud Althunibat; Sezer C. Tokgoz; Serhan Yarkan; Scott L. Miller; Khalid A. Qaraqe (IEEE Access, 2023)
Hybrid free-space optical (FSO) and millimeter wave (mmWave) systems have been proposed as an efficient solution to improve spectral efficiency and maintain link reliability. The comparable supported data rate and the complementary characteristics in different weather conditions of both links, i.e., FSO and mmWave) have attracted research efforts towards analyzing the different performance aspects of hybrid FSO-mmWave systems. Following this direction, in this article, the physical-layer security analysis of the dual-hop hybrid FSO-mmWave systems is addressed. In the considered system, both FSO and mmWave links are simultaneously used to carry data at each hop, while an eavesdropper is assumed to present to wiretap either one or both links. The analysis includes building a mathematical framework to derive different secrecy metrics, such as the average secrecy capacity, secrecy outage probability and effective secrecy throughput metrics, in mathematical expressions. Obtained analytical results are verified using Monte Carlo simulations where exact matching are achieved. Moreover, the presented results include investigation of the impact of the different operational parameters on the overall secrecy performance.